2020
DOI: 10.1038/s41467-019-13925-5
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of chirality and structural complexity in single crystals at the molecular and morphological levels

Abstract: Naturally occurring single crystals having a multidomain morphology are a counterintuitive phenonomon: the macroscopic appearance is expected to follow the symmetry of the unit cell. Growing such crystals in the lab is a great challenge, especially from organic molecules. We achieve here uniform metallo-organic crystals that exhibit single crystallinity with apparently distinct domains and chirality. The chirality is present at both the molecular and macroscopic levels, although only achiral elements are used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 45 publications
9
91
2
1
Order By: Relevance
“…We previously reported the formation of paradoxical multidomain single crystals formed from a similar ligand (having triple instead of double carbon–carbon bonds) and Cu(NO 3 ) 2 . 66 Although morphologically completely different, these crystals have a molecular packing nearly identical to the crystals reported here. These observations show that varying the anion (Br – , Cl – , NO 3 – , and OAc – ) and metal cation (Cu vs Ni) in the presence of these ligands results in varied morphologies (shape, mono- to multidomain) and dimensions while retaining a high level of uniformity and nearly identical crystallographic structures.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…We previously reported the formation of paradoxical multidomain single crystals formed from a similar ligand (having triple instead of double carbon–carbon bonds) and Cu(NO 3 ) 2 . 66 Although morphologically completely different, these crystals have a molecular packing nearly identical to the crystals reported here. These observations show that varying the anion (Br – , Cl – , NO 3 – , and OAc – ) and metal cation (Cu vs Ni) in the presence of these ligands results in varied morphologies (shape, mono- to multidomain) and dimensions while retaining a high level of uniformity and nearly identical crystallographic structures.…”
Section: Resultssupporting
confidence: 60%
“…The use of different coordinative counteranions (Br – , Cl – , NO 3 – , and OAc – ), metal cations (Ni 2+ , Cu 2+ ), growth conditions, and similar ligands (having triple instead of double carbon–carbon bonds) results in nearly identical chiral framework structures. 66 These observations indicate that a new class of chiral crystals is achievable using metal cations known to form an octahedral molecular geometry with four pyridine moieties in plane. Although the crystallographic structures are nearly identical, the crystals can take on many sizes and forms, ranging from achiral mono- to chiral multidomain morphologies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The shaping processes are mainly restricted to crystals with canonical frameworks and their fundamental aspects are poorly understood 20 . Our group has recently shown that a variability of uniform metallo-organic crystals with different morphologies can be obtained 28 30 . These studies include the formation of a unique yoyo -shaped, single crystal exhibiting both a multidomain and chiral morphology 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the difference in the relative growth rate between the (111) face and the (100) face becomes small with time and the size of the crystals tends to be more uniform. We learn that the reaction process of nucleus growth is mainly controlled by thermodynamics, [ 37 ] so the (100) faces with lower surface energy are more thermodynamically stable, while the (111) faces will be dissolved during the reaction due to its instability. Therefore, eight corners of the PBA‐I corresponding to the (111) face are selectively etched to give a type of cross‐sectional crystal of PBA‐II.…”
Section: Resultsmentioning
confidence: 99%